An FRMD4B variant suppresses dysplastic photoreceptor lesions in models of enhanced S-cone syndrome and of Nrl deficiency - Kong, Yang (Hum Mol Genet, 2018)
Photoreceptor dysplasia, characterized by formation of folds and (pseudo-)rosettes in the outer retina, is associated with loss of functional nuclear receptor subfamily 2 group E member 3 (NR2E3) and neural retina leucine-zipper (NRL) in both humans and mice. A sensitized chemical mutagenesis study to identify genetic modifiers that suppress photoreceptor dysplasia in Nr2e3(rd7)mutant mice identified line Tvrm222, which exhibits a normal fundus appearance in the presence of the rd7 mutation. The Tvrm222 modifier of Nr2e3(rd7/rd7) was localized to Chromosome 6 and identified as a missense mutation in the FERM domain containing 4B (Frmd4b) gene. The variant is predicted to cause the substitution of a serine residue 938 with proline (S938P). The Frmd4b(Tvrm222) allele was also found to suppress outer nuclear layer (ONL) rosettes in Nrl(–/–) mice. Fragmentation of the external limiting membrane (ELM), normally observed in rd7 and Nrl(–/–)mouse retinas, was absent in the presence of the Frmd4b(Tvrm222) allele. FRMD4B, a binding partner of cytohesin 3, is proposed to participate in cell junction remodeling. Its biological function in photoreceptor dysplasia has not been previously examined. In vitro experiments showed that the FRMD4B(938P) variant fails to be efficiently recruited to the cell surface upon insulin stimulation. In addition, we found a reduction in protein kinase B phosphorylation and increased levels of cell junction proteins, Catenin beta 1 and tight junction protein 1, associated with the cell membrane in Tvrm222 retinas. Taken together, this study reveals a critical role of FRMD4B in maintaining ELM integrity and in rescuing morphological abnormalities of the ONL in photoreceptor dysplasia.